IHSAN: A Secure and Transparent Crowdfunding Platform Leveraging Comprehensive Decentralized Technologies - Omar Khalid Alia; Duaa Mohammad Suleiman; Haitham Ameen Noman (IEEE Access)
Traditional centralized crowdfunding platforms enable individuals and organizations to raise capital online but often struggle with trust, transparency, and accountability due to centralized control and opaque governance. These issues lead to user skepticism and reduced engagement. This paper introduces IHSAN, a decentralized crowdfunding platform leveraging blockchain technology to ensure decentralized control, immutable transactions, and transparent records. Integrating decentralized database technology dubbed “BigchainDB”, IHSAN enhances scalability and data query efficiency while maintaining security. Eliminating centralized control empowers donors and beneficiaries with greater accountability and trust in fund allocation and project execution. Our results demonstrate that IHSAN reduces platform fees to as low as 1%, significantly lower than the approximately 8% and 2.9% charged by traditional platforms. It also achieves faster transaction times of around 2 minutes, compared to up to 14 days or 2–5 days for conventional platforms. Additionally, IHSAN overcomes geographic limitations by offering unrestricted global access, improving donor confidence, and increasing project success rates.